Hourly Surface Observations Suggest Stronger Solar Dimming and Brightening at Sunrise and Sunset Over China. Issue 2 (25th January 2021) - Wang, Yawen; Zhang, Jiahua; Sanchez‐Lorenzo, Arturo; Tanaka, Katsumasa; Trentmann, Jörg; Yuan, Wenping; Wild, Martin
Abstract: Exploration of the diurnal pattern of global dimming and brightening has been limited by the paucity of high‐temporal resolution observations. Based on 22 years' continuous observations of hourly surface solar radiation (SSR) over 96 stations across China for 1993–2014, this study evidences higher relative changes in diurnal SSR in terms of both frequency and magnitude at sunrise and sunset, with a longer pathway for the sun passing through the atmosphere, than the hours in between. This, in general, leads to a further shortening of the days between sunrise and sunset in the cold seasons and the polluted region of north China with low radiation levels but a further extension in the other seasons and regions with sufficient sunlight. Pollution reduction by 39.4%–69.7% during the 2014 Asia‐Pacific Economic Cooperation summit at Beijing are accompanied with a 10.4–80.0% rebound of diurnal SSR in the forenoon and late afternoon. Plain Language Summary: As the primary energy source for our planet, solar radiation received at the Earth's surface, i.e., surface solar radiation (SSR), has undergone significant decadal changes. But at which specific time of the day does such change mostly occur remains a question, due to the limited SSR data at hourly or shorter timescales. Since 1993, China automated its measuring instruments and started continuous hourly SSR observations. Using these historical data records, this study evidences that the largest changes in SSR occur at the hours close to sunset and sunrise, which is also known as the early morning and late afternoon rush hours. The detected dimming and brightening of SSR at sunset and sunrise could affect the period of daytime, respectively, resulting in a further shortening of the days in cold seasons and polluted regions but a further extension in the other seasons and regions with sufficient sunlight. The emission reduction campaign directed by the Chinese government during the 2014 Asia‐Pacific Economic Cooperation (APEC) summit at Beijing has remarkably induced an increase in the diurnal cycle of SSR, especially in the forenoon and late afternoon as compared to the Pre‐APEC period, contrary to the normal changes solely driven by solar cycle. Key Points: Daytime‐dependent dimming and brightening in surface solar radiation is most clearly imprinted near sunrise and sunset over China Daytime shortens in the cold seasons and polluted regions of China but further prolongs in the other seasons and regions since 1993 The 2014 APEC Blue phenomenon at Beijing induced a change in the diurnal cycle of surface solar radiation